Seamless horizontal handover algorithm for homogeneous wireless mobile networks using fuzzy logic - Ibrahim, Mohammed Khaleel (2013)
The wireless networks of the near future will be capable of successfully handling various kinds of communication systems. Worldwide Interoperability for Microwave Access (referred to as WiMAX) is a physical layer wireless communications technology for outdoor broadband wireless coverage. The most important and society application of WiMAX is the mobile communication. When a mobile station changes its geographical position, it may also need to change its attachment point in the network in order to retain the quality of the connection. Currently, the mobility of a terminal is a requirement of great importance, supported by a procedure known as handover. One of the main challenges for robust mobility is the availability of simple and seamless handover algorithms, which allow a mobile node to connect among homogeneous or heterogeneous wireless networks. Two types of handover could take place: horizontal handover between wireless Access Points at the same wireless network, and vertical handover between different wireless networks. During the handover procedure the mobile node can neither send nor receive any data packets. This results in packet delay and in some cases packet loss. This project proposes an efficient horizontal handover decision based on fuzzy logic principle in order to decrease unnecessary handover. Three systems used in this studying to know which one can obtain the best results system A , system B and system C plus applying the eight steps of horizontal handover scenario on each system. System A used three parameters : Received Signal Strength ( RSS ), Available BandWidth ( ABW ) and Bit Error Rate ( BER ) , System B used two parameters : RSS , ABW while system C used the conventional method. After comparison between the three systems, it is observed that system A is the best scenario among the three. The result shows that by using this method, handover number and the time delay was reduced plus a decrease in proper lost calls number.